X-ray spectra of plasma radiation from laser induced low-power vacuum discharge. (7th December 2017) - Romanov, I V; Kologrivov, A A; Paperny, V L; Rupasov, A A; Starodub, A N
Abstract: The x-ray spectra of plasma radiation in the wavelength range 30–300 Å are studied. The radiation is emitted from plasma of a vacuum discharge with storage energy less than 30 J that is initiated on an Al or Fe cathode by beam from neodymium laser with a power density up to 10 12 W cm −2 . It is shown that both the spectral composition and intensity of radiation of hot micropinch plasma that is formed in the cathodic jet are determined by the set of the discharge and the laser pulse characteristics. By optimizing these characteristics, a mode of the discharge operation is attainable, in which a significant portion of the radiation energy is located in the long-wave band of the quasi-continuum (230–270 Å and 160–200 Å for Al and Fe cathodes, respectively). That makes it possible to treat such a discharge as an intense source of narrow-band soft x-ray radiation.